Preparation method and application of a novel zero-dimensional indium-based hybrid metal halide crystal

CN122977979APending Publication Date: 2026-10-27GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611178802.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

目前,以[InCl5]2-为发光中心的零维铟基卤化物发光材料鲜有报道

Benefits of technology

1)本发明提供了一种全新的材料结构,以[InCl5]2-三角双锥体为发光中心的零维杂化金属卤化物 PTA2InCl5。该结构突破了现有铟基卤化物中[InCl6]3-八面体占主导的局限性,为非铅金属卤化物发光材料开辟了新的结构拓扑类型,丰富了该领域的材料体系;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977979A_ABST
    Figure CN122977979A_ABST
Patent Text Reader

Abstract

This invention discloses a novel method for preparing and applying zero-dimensional indium-based hybrid metal halide crystals, belonging to the field of luminescent materials technology; the chemical formula of this material is PTA₂InCl₅, wherein PTA… + It is an organic cation, and its crystal structure consists of two [InCl5] groups. 2‑ It is composed of alternating trigonal bipyramidal structures and organic cations, unlike the common [InCl6]. 3‑ This material has an octahedral configuration and emits blue light when excited by ultraviolet light, achieved by doping with Sb. 3+ The emission color can be adjusted to achieve blue-orange dual-spectral emission. 3+ When the doping amount is 5 mol%, the photoluminescence quantum yield can reach 60.3%. The preparation process of this invention is simple, the raw materials are environmentally friendly and inexpensive, and the antimony doping enriches the luminescence properties of indium-based hybrid metal halides, improves their fluorescence quantum yield, and solves the problem of the single color of light emission of single-component hybrid metal halides. It has good application prospects in solid-state lighting and fluorescent anti-counterfeiting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lead-free zero-dimensional metal halide luminescent materials, specifically to a method for preparing and applying a novel zero-dimensional indium-based hybrid metal halide crystal. Background Technology

[0002] In recent years, lead-based halide perovskite materials have become a research hotspot in the field of luminescence due to their excellent photoelectric properties, such as high photoluminescence quantum yield and tunable bandgap. However, the toxicity of lead and the poor stability of lead-based perovskite materials in humid and hot environments severely limit their commercial applications. Therefore, developing non-toxic or low-toxic, stable non-lead halide luminescent materials is of great significance. Indium (In), as a Group 3 element, is environmentally friendly and non-toxic. Meanwhile, indium-based halide materials possess good stability and tunable optical properties, making them one of the most ideal alternatives to lead-based halide perovskites. Currently, in the reported zero-dimensional indium-based halide luminescent materials, indium ions mainly exist as [InCl6]. 3- The octahedral coordination form exists, and these inorganic octahedral structures are very likely to form self-trapped excitons (STEs), thereby generating characteristic broadband luminescence.

[0003] In indium-based metal halides, the five-coordinate trigonal bipyramidal configuration ([InCl5)) 2- Extremely rare. Currently, [InCl5] is the most common. 2- Zero-dimensional indium halide luminescent materials with luminescence centers are rarely reported. Compared with the octahedral configuration, the trigonal bipyramidal configuration has lower symmetry, which may lead to different electronic structures and luminescence behaviors than the octahedral configuration. Therefore, developing indium-based metal halide materials with trigonal bipyramidal configurations is of great significance for enriching the structural types of non-lead zero-dimensional metal halide luminescent materials and exploring novel luminescence mechanisms.

[0004] Furthermore, research shows that ion doping can effectively control the electronic structure and excited-state dynamics of metal halide materials. Among them, Sb... 3+ Doping can significantly improve the luminescence efficiency of materials; by adjusting the doping concentration to coordinate the emission spectrum, high-efficiency luminescence can be achieved. Therefore, developing Sb... 3+ Novel doped indium-based metal halide materials are expected to significantly improve their luminescence performance while maintaining structural novelty, providing a new approach for the practical application of lead-free zero-dimensional metal halide luminescent materials. Summary of the Invention

[0005] This invention addresses the technical problems of high toxicity and low stability of existing lead-based halide perovskite materials, as well as the limited structural diversity and luminous efficiency of existing non-lead indium-based halide materials. It provides a novel method for preparing and applying zero-dimensional indium-based hybrid metal halide crystals, and for the first time designs and synthesizes a [InCl5]-based [InCl5]-based [InCl5]-based hybrid metal halide crystal.2- The zero-dimensional structural material PTA2InCl5 with a triangular bipyramidal luminescent center was obtained through Sb 3+ By doping to regulate its luminescence properties, color coordination was achieved, moving from single blue light emission to a dual blue-orange emission peak.

[0006] To achieve the above technical effects, the following technical solution is adopted: A novel zero-dimensional indium-based hybrid metal halide crystal material with the chemical formula PTA2InCl5, wherein PTA represents a phenyltrimethylammonium cation; Furthermore, the PTA2InCl5 belongs to the triclinic crystal system, space group P-1, and is an isolated [InC15]. 2- PTA + They are spaced apart to form a zero-dimensional structure; [InCl5] in PTA2InCl5 2- It has two configurations, with each In atom having five Cl atoms. - The ion is [InCl5]. 2- The coordination is in the form of a triangular bipyramidal structure; its cell parameters are a = 9.5671(4) Å, b = 15.0839(5) Å, c = 17.3757(6) Å; α = 84.291(1)°, β = 79.276(1)°, γ = 84.946(1)°; Furthermore, the material emits blue light under ultraviolet light excitation, with an emission peak at 475 nm and a photoluminescence quantum yield of 3.1%.

[0007] This invention also provides a method for preparing the above-mentioned novel zero-dimensional indium-based hybrid metal halide crystal material, comprising the following steps: Step S1: Add phenyltrimethylammonium chloride and indium chloride to an organic solvent at a molar ratio of 2~6:1 to prepare a mixed solution; Step S2: Stir the mixed solution obtained in step S1 at 70~90℃ for 5~20 min until a clear solution is formed. Filter the reaction solution to remove insoluble impurities and cool it. Step S3: Let the cooled reaction solution stand for 5-8 days until blocky crystals precipitate. Separate the blocky crystals, wash and dry them to obtain PTA2InCl5 crystal material.

[0008] The present invention also provides an Sb 3+ PTA2InCl5 doped crystal material, Sb 3+ Ionic substitution of In in PTA2InCl5 in claims 1-4 3+The lattice positions of the ions are maintained, and the crystal structure is identical to that of undoped PTA₂InCl₅. The chemical formula of the doped product is: PTA₂InCl₅: xSb 3+ x is: 0 < x ≤0.07; Furthermore, the material exhibits dual emission peaks under 315 nm ultraviolet light excitation, with the emission peaks located at 485 nm and 625 nm, respectively. The present invention also provides the above-mentioned Sb 3+ A method for preparing PTA2InCl5 doped crystal material includes the following steps: Step C1: Phenylacetyltrimethylammonium chloride C9H 14 A mixed solution is prepared by adding NCl, indium chloride (InCl3), and antimony chloride (SbCl3) to an organic solvent at a molar ratio of 2-6: 1: 0.03-0.2. Step C2: Stir the mixed solution obtained in step C1 at 70~90℃ for 5~20 min until a clear solution is formed. Filter the reaction solution to remove insoluble impurities and cool it. Step C3: After the cooled reaction solution has been allowed to stand for 3-5 days, the precipitated product is separated, washed, and dried to obtain Sb. 3+ PTA2InCl5 doped crystal material; Furthermore, the organic solvent is selected from one or more of methanol, concentrated hydrochloric acid, ethanol, isopropanol, and N,N-dimethylformamide.

[0009] Furthermore, the drying conditions are: a drying temperature of 60~90℃ and a drying time of 6~15 h.

[0010] The present invention also provides the above-mentioned PTA2InCl5 crystal material or the above-mentioned Sb 3+ Applications of PTA2InCl5 doped crystal materials in solid-state lighting or fluorescent anti-counterfeiting.

[0011] The beneficial effects of this invention are as follows: 1) This invention provides a novel material structure, using [InCl5] 2- PTA₂InCl₅ is a zero-dimensional hybrid metal halide with a trigonal bipyramidal luminescent center. This structure breaks through the limitations of existing indium-based halides such as [InCl₆]. 3- The dominance of octahedral structures has opened up new structural topologies for non-lead metal halide luminescent materials, enriching the material system in this field. 2) Through Sb 3+By doping PTA2InCl5, the luminescence characteristics of the material were successfully modulated from a single-peak blue light to a double-peak emission covering both blue and orange light, which improved the fluorescence quantum yield and solved the problem of single-component indium-based hybrid metal halides. The double emission characteristics have great potential in solid-state lighting and fluorescent anti-counterfeiting. 3) This invention uses a solvent evaporation method for synthesis, which is simple, mild, has a low reaction temperature, and is inexpensive. Attached Figure Description

[0012] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0013] Figure 1 This is a crystal structure diagram of the intrinsic zero-dimensional indium-based hybrid metal halide crystal material prepared in Example 1 of the present invention; Figure 2 The powder XRD diffraction pattern of the intrinsic zero-dimensional indium-based hybrid metal halide crystal material prepared in Example 1 of this invention; Figure 3 This is a physical crystal image of the intrinsic zero-dimensional indium-based hybrid metal halide crystal material prepared in Example 1 of the present invention; Figure 4 The excitation spectrum (PLE) and emission spectrum (PL) of the intrinsic zero-dimensional indium-based hybrid metal halide crystal material prepared in Example 1 of this invention are shown. Figure 5 Different proportions of Sb were prepared for Example 2 of the present invention. 3+ Powder XRD diffraction pattern of doped zero-dimensional indium-based hybrid metal halide crystal material; Figure 6 Preparation of 5% Sb in Example 2 of the present invention 3+ Excitation (PLE) and emission (PL) spectra of doped zero-dimensional indium-based hybrid metal halide crystal materials; Figure 7 5% Sb was prepared for Example 3 of the present invention. 3+ CIE color coordinate diagram and LED device illustration of doped zero-dimensional indium-based hybrid metal halide crystal material. Detailed Implementation

[0014] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0015] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0016] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments of the present invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, and / or combinations thereof.

[0017] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the art; unless otherwise specified, the experimental methods and techniques used are conventional methods and techniques in the art.

[0018] The technical solutions provided by the present invention will be described below with reference to the embodiments. The scope of protection of the present invention is not limited by the following embodiments.

[0019] Example 1: Preparation of PTA2InCl5 crystal material Five commonly used laboratory solvents (methanol, concentrated hydrochloric acid, ethanol, isopropanol, and N,N-dimethylformamide) were selected for a selective screening experiment. Through comparative experiments, methanol was ultimately determined to be the optimal solvent. 8 mmol of C9H... 14 NCl, 2 mmol of InCl3, and 2.1 mL of methanol were sequentially added to a 20 mL serum bottle. The bottle was placed on a magnetic stirrer and heated to 90 °C at 400 rpm / min. After stirring for about 10 min, a clear solution was formed. The solution was then filtered while hot to remove insoluble impurities. The filtrate was transferred to a clean serum bottle, boiled open for about 7 min, and then allowed to cool naturally to room temperature. After standing for 7 days, transparent blocky crystals precipitated. Finally, the crystals were filtered and washed three times with acetone, then dried in a vacuum drying oven at 60 °C for 12 h to obtain PTA2InCl5 crystalline material.

[0020] The obtained crystals possess good morphology and crystallinity, making them suitable for subsequent structural characterization and performance testing. For example... Figure 1 As shown, single-crystal XRD diffraction and crystal analysis revealed its crystal structure as PTA2InCl5, belonging to the triclinic crystal system, space group P-1, and an isolated [InC15]. 2- PTA + They are spaced apart to form a zero-dimensional structure; and two configurations of [InCl5] exist. 2-Each In atom is associated with five Cl atoms. - Ion coordination forms a trigonal bipyramidal configuration; specifically, for [In(1)Cl5] 2- The configuration has In(1)-Cl bond lengths ranging from 2.3976(9) to 2.5015(8) Å, and an axial bond angle (Cl-In(1)-Cl) of 171.85(3)°; for [In(2)Cl5] 2- The configuration shows that the In(2)-Cl bond length ranges from 2.4064(8) to 2.5170(7) Å, and the axial bond angle (Cl-In(2)-Cl) is 176.74(3)°; this indicates that the two [InCl5] configurations have different bond lengths. 2- All triangular bipyramidal configurations exhibit high degrees of distortion. For example... Figure 2 As shown, the XRD pattern of the single crystal simulation and the powder XRD diffraction pattern are... Figure 1 This indicates that the PTA2InCl5 crystal material has high phase purity and good crystallinity. For example... Figure 3 As shown, the material has a crystal size of 4 mm, is in bulk form, and emits blue fluorescence under 365 nm ultraviolet light excitation. Its fluorescence quantum yield was measured to be 3.1% using absolute fluorescence quantum yield spectroscopy. Figure 4 As shown, within the excitation wavelength range of 285~385 nm, the emission peak of the material is located at 475 nm, exhibiting blue light, and redshifts with increasing excitation wavelength, indicating that its emission is wavelength-dependent.

[0021] Example 2: Preparation of 5% Sb 3+ PTA2InCl5 doped crystal material In the glove box, weigh out 8 mmol of C9H 14 The reactants were NCl, 1.9 mmol of InCl3, and 0.1 mmol of SbCl3. The reactants were then dissolved in 2.1 mL of methanol and heated and stirred on a magnetic stirrer (90°C, 400 rpm / min) for approximately 8 min. Once a clear solution was formed, it was immediately filtered while hot to remove impurities. The solution was then heated to boiling for 7 min in an open container, allowed to cool naturally to room temperature, and left to stand for 4 days. The precipitated product was then separated by vacuum filtration, washed three times with acetone, and dried in a vacuum drying oven at 60°C for 12 h to finally obtain PTA2InCl5: 5%SbCl3. 3+ Crystals; different proportions (3%, 7%) of Sb 3+ The experimental procedure for doped PTA2InCl5 crystal materials is the same as described above.

[0022] like Figure 5 As shown, different proportions of Sb 3+The XRD diffraction peaks of the doped PTA₂InCl₅ crystal and the undoped PTA₂InCl₅ crystal are in perfect agreement, indicating that Sb 3+ Ionized In 3+ The lattice position of ions does not disrupt the crystal structure. For example... Figure 6 Spectroscopic results show that under 315 nm excitation, the material exhibits dual emission behavior: blue light emission at 485 nm originates from the singlet STE state, and orange light emission at 625 nm originates from the triplet STE state, with the latter being the dominant emission peak and exhibiting a significantly higher fluorescence intensity than the former. Furthermore, PTA2InCl5: 5%Sb 3+ The PLQY reached 60.3%, higher than the quantum yield of PTA2InCl5 crystal, indicating that Sb 3+ Doping strategies can significantly improve the luminescence properties of materials.

[0023] Example 3: Fabrication of LED Devices LED devices were fabricated using a 310 nm ultraviolet chip. The process involved mixing PTA₂InCl₅ with 5% Sb. 3+ The sample powder was thoroughly ground and then mixed evenly with a self-made polystyrene (PS) curing adhesive. The mixture was then coated onto the surface of a 310 nm UV chip. Finally, the LED was dried in an oven at 80°C for 6 hours to obtain the LED device. Figure 7 As shown, after the LED beads are lit, the emission color coordinates of the obtained sample are CIE (0.46, 0.37), the correlated color temperature (CCT) is 2399 K, and the color rendering index (CRI) is 80.45, which has potential application value in warm white solid-state lighting devices.

[0024] Therefore, those skilled in the art will recognize that although embodiments of the present invention have been shown and described in detail herein, many other variations or modifications conforming to the principles of the present invention can be directly determined or derived from the disclosure of the present invention without departing from the spirit and scope of the invention. Thus, the scope of the present invention should be understood and construed as covering all such other variations or modifications.

Claims

1. A novel zero-dimensional indium-based hybrid metal halide crystal material, characterized in that, The chemical formula is PTA2InCl5, where PTA represents phenyltrimethylammonium cation.

2. The novel zero-dimensional indium-based hybrid metal halide crystal material as described in claim 1, characterized in that, The PTA2InCl5 belongs to the triclinic crystal system, space group P-1, and is an isolated [InC15]. 2- PTA + They are spaced apart from each other, forming a zero-dimensional structure; [InCl5] in PTA2InCl5 2- It has two configurations, with each In atom having five Cl atoms. - The ion is [InCl5]. 2- Coordination in the form of a triangular bipyramidal structure.

3. The novel zero-dimensional indium-based hybrid metal halide crystal material as described in claim 1, characterized in that, The material emits blue light under ultraviolet light excitation, with an emission peak at 475 nm and a photoluminescence quantum yield of 3.1%.

4. The method for preparing a novel zero-dimensional indium-based hybrid metal halide crystal material as described in claims 1-3, characterized in that, Includes the following steps: Step S1: Add phenyltrimethylammonium chloride and indium chloride to an organic solvent at a molar ratio of 2~6:1 to prepare a mixed solution; Step S2: Stir the mixed solution obtained in step S1 at 70~90℃ for 5~20 min until a clear solution is formed. Filter the reaction solution to remove insoluble impurities and cool it. Step S3: Let the cooled reaction solution stand for 5-8 days until blocky crystals precipitate. Separate the blocky crystals, wash and dry them to obtain PTA2InCl5 crystal material.

5. A type of Sb 3+ PTA2InCl5 doped crystal material, characterized in that, Sb 3+ Ionic substitution of In in PTA2InCl5 in claims 1-4 3+ The lattice positions of the ions are maintained, and the crystal structure is identical to that of undoped PTA₂InCl₅. The chemical formula of the doped product is: PTA₂InCl₅: xSb 3+ x is: 0 < x ≤ 0.

07.

6. An Sb as described in claim 5 3+ PTA2InCl5 doped crystal material, characterized in that, The material exhibits dual emission peaks under 315 nm ultraviolet light excitation, with the emission peaks located at 485 nm and 625 nm, respectively.

7. An Sb as described in claims 5-6 3+ The method for preparing PTA2InCl5 doped crystal material is characterized by, Includes the following steps: Step C1: Phenylacetyltrimethylammonium chloride C9H 14 A mixed solution is prepared by adding NCl, indium chloride (InCl3), and antimony chloride (SbCl3) to an organic solvent at a molar ratio of 2-6: 1: 0.03-0.

2. Step C2: Stir the mixed solution obtained in step C1 at 70~90℃ for 5~20 min until a clear solution is formed. Filter the reaction solution to remove insoluble impurities and cool it. Step C3: After the cooled reaction solution has been allowed to stand for 3-5 days, the precipitated product is separated, washed, and dried to obtain Sb. 3+ PTA2InCl5 doped crystal material.

8. The preparation method according to claim 4 or claim 7, characterized in that, The organic solvent is selected from one or more of methanol, concentrated hydrochloric acid, ethanol, isopropanol, and N,N-dimethylformamide.

9. The preparation method according to claim 4 or claim 7, characterized in that, The drying conditions are: drying temperature of 60~90℃ and drying time of 6~15 h.

10. A novel zero-dimensional indium-based hybrid metal halide crystal material as described in claim 1, or an Sb crystal material as described in claim 5. 3+ Applications of PTA2InCl5 doped crystal materials in solid-state lighting or fluorescent anti-counterfeiting.